A Framework for Managing Knowledge and Competencies in a Group Project Implementation - A. Jabar, Marzanah (2007)
Every organisation realizes that its organisational knowledge which resides in individual brain or stored in organisational processes, products, facilities, systems and documentation is quickly becoming a sustainable competitive advantage. This growing attention has lead to the idea that these resources must be protected, cultivated and shared among its members. As organisation's knowledge is built upon these human resources, and effective way of managing these resources is a challenge. The challenges poses problems such as when knowledge can be lost when people leave the organisation, problem in difficulties to manage tacit knowledge and also in managing the competencies, expertise and capabilities of the organisation. The research has explored and proposed a framework to achieve its objectives, in capturing, and structuring knowledge in acquiring competitiveness edge in an organisation. KEPSNet (Knowledge Extract,Profiling, and Sharing Network), has approached the problems in managing knowledge and competencies based on three key elements of peopleprocess- product, conceptual theory and by prescribing a knowledge model of five layers: knowledge object, agents, knowledge functionalities, knowledge services and knowledge application. KEPSNet provided a practical application of knowledge capture and reuses of relevant know-how, experiences, best practices from a group project implementation. KEPSNet implementation as a Portal provided functionalities, for group project to capture and retain their knowledge in group repository with the use of concept maps, thus providing facilities for retrieving and sharing knowledge, structured and retained in the group knowledge repository. Two software agents introduced in KEPSNet implementation: the Profile Agent and Knowledge Agent has shown that it has adopted an autonomous way of managing knowledge, maintaining competency profile to reflect the level of knowledge of the expertise and to support knowledge sharing during group project implementation. KEPSNet Portal and agents were developed on Domino Lotus Notes, while Cmap Tool was used as the knowledge modeling tool for knowledge capture in this research